Peran KKG dalam Penguatan Kompetensi Profesional Guru SD di Gugus Diponegoro Korwilcam Dinas Pendidikan dan Kebudayaan Karangmoncol Purbalingga - Kusno; Novan Ardy Wiyani; Made Yudhi Setiani (Jurnal Kependidikan, 2022)
This research is a case study research aimed at analyzing the role of the teacher working group (KKG) in strengthening the professional competence of elementary school teachers in the Diponegoro Cluster Korwilcam Education and Culture Office of Karangmoncol Purbalingga. Data were collected using interview, observation and documentation techniques and then analyzed using three stages, namely data reduction, data display and verification. The results showed that with the various activities carried out by the KKG, the teachers already had the ability to master the material and scientific mindset that supported the subjects they taught, the teachers were able to organize fun learning activities, were able to conduct classroom action research as a reflective effort from the activities. learning that has been held, and able to utilize information and communication technology to organize innovative learning activities.